<h2>
Hello!</h2>
The answer is: ![g(x)=-\sqrt[3]{x-1}](https://tex.z-dn.net/?f=g%28x%29%3D-%5Csqrt%5B3%5D%7Bx-1%7D)
<h2>
Why?</h2>
Let's check the roots and the shown point in the graphic (2,-1)
First,
![0=-\sqrt[3]{x-1}\\\\0^{3}=(-\sqrt[3]{x-1})^{3}\\\\0=-(x-1)\\\\x=1](https://tex.z-dn.net/?f=0%3D-%5Csqrt%5B3%5D%7Bx-1%7D%5C%5C%5C%5C0%5E%7B3%7D%3D%28-%5Csqrt%5B3%5D%7Bx-1%7D%29%5E%7B3%7D%5C%5C%5C%5C0%3D-%28x-1%29%5C%5C%5C%5Cx%3D1)
then,
![g(0)=-\sqrt[3]{0-1}\\g(0)=-(-1)\\g(0)=1\\y=1](https://tex.z-dn.net/?f=g%280%29%3D-%5Csqrt%5B3%5D%7B0-1%7D%5C%5Cg%280%29%3D-%28-1%29%5C%5Cg%280%29%3D1%5C%5Cy%3D1)
So, we know that the function intercepts the axis at (1,0) and (0,1), meaning that the function match with the last given option
(
)
Second,
Evaluating the function at (2,-1)
![y=-\sqrt[3]{x-1}\\-1=-\sqrt[3]{2-1}\\-1=-\sqrt[3]{1}\\-1=-(1)\\-1=-1](https://tex.z-dn.net/?f=y%3D-%5Csqrt%5B3%5D%7Bx-1%7D%5C%5C-1%3D-%5Csqrt%5B3%5D%7B2-1%7D%5C%5C-1%3D-%5Csqrt%5B3%5D%7B1%7D%5C%5C-1%3D-%281%29%5C%5C-1%3D-1)
-1=-1
It means that the function passes through the given point.
Hence,
The equation which represents g(x) is ![g(x)=-\sqrt[3]{x-1}](https://tex.z-dn.net/?f=g%28x%29%3D-%5Csqrt%5B3%5D%7Bx-1%7D)
Have a nice day!
Answer:
B
Step-by-step explanation:
given
- 4x²(3x - 7)
multiply each term in the parenthesis by - 4x²
= (-4x² × 3x) + ( - 4x² × - 7)
= - 12x³ + 28x² → B
Answer:
![a_9=48](https://tex.z-dn.net/?f=a_9%3D48)
Step-by-step explanation:
we are given
sequence is geometric
so, we can use nth term formula
![a_n=a_1(r)^{n-1}](https://tex.z-dn.net/?f=a_n%3Da_1%28r%29%5E%7Bn-1%7D)
we have
![a_1=3](https://tex.z-dn.net/?f=a_1%3D3)
![r=\sqrt{2}](https://tex.z-dn.net/?f=r%3D%5Csqrt%7B2%7D)
we have to find a9
so, we can plug n=9
we get
![a_9=3(\sqrt{2})^{9-1}](https://tex.z-dn.net/?f=a_9%3D3%28%5Csqrt%7B2%7D%29%5E%7B9-1%7D)
![a_9=2^4\cdot \:3](https://tex.z-dn.net/?f=a_9%3D2%5E4%5Ccdot%20%5C%3A3)
![a_9=48](https://tex.z-dn.net/?f=a_9%3D48)
Answer:
51
Step-by-step explanation:
See the other answer